Multi Stage Power Generation in An Open Canal System by Accelerated Flow (Journal of Informatics and Mathematical Sciences, 2018)
The present work considers the possibility of using river currents to generate electric power in order to supplement existing power units. A physical system consisting of a flowing river/canal with rectangular cross section, an open channel nozzle, and an impact turbine is modelled mathematically. The model is simulated using MATLAB for varying slopes and two nozzle-turbine sequences. It is found that the usage of nozzles demonstrably increases the velocity, and therefore, the kinetic energy of the flow. A total power ranging from 0.34 to 10.79MW for the lowest and highest value of slope, respectively, is predicted by the model. Possible applications are discussed.
Keywords: Open canal; Numerical model; Nozzles; Cross flow turbine; Power generation